Identification and characterization of the SnTox6-Snn6 interaction in the Parastagonospora nodorum-wheat pathosystem - Gao, Y.; Faris, J.; Liu, Z.; Kim, Y.; Syme, Robert; Oliver, Richard; Xu, S.; Friesen, T. (American Phytopathological Society, 2015)
Parastagonospora nodorum is a necrotrophic fungal pathogen that causes Septoria nodorum blotch (SNB) (formerly Stagonospora nodorum blotch) on wheat. P. nodorum produces necrotrophic effectors (NE) that are recognized by dominant host sensitivity gene products resulting in disease development. The NE-host interaction is critical to inducing NE-triggered susceptibility (NETS). To date, seven NE-host sensitivity gene interactions, following an inverse gene-for-gene model, have been identified in the P. nodorum-wheat pathosystem. Here, we used a wheat mapping population that segregated for sensitivity to two previously characterized interactions (SnTox1-Snn1 and SnTox3-Snn3-B1) to identify and characterize a new interaction involving the NE designated SnTox6 and the host sensitivity gene designated Snn6. SnTox6 is a small secreted protein that induces necrosis on wheat lines harboring Snn6. Sensitivity to SnTox6, conferred by Snn6, was light-dependent and was shown to underlie a major disease susceptibility quantitative trait locus (QTL). No other QTL were identified, even though the P. nodorum isolate used in this study harbored both the SnTox1 and SnTox3 genes. Reverse transcription-polymerase chain reaction showed that the expression of SnTox1 was not detectable, whereas SnTox3 was expressed and, yet, did not play a significant role in disease development. This work expands our knowledge of the wheat-P. nodorum interaction and further establishes this system as a model for necrotrophic specialist pathosystems.